Picking up the Pieces from the Bottom and Political Development in Pakistan from 1951-55 - Haider, Zulqarnain; Abbas Khan, Amjad (Al-Amīr Research Journal for Islamic Studies, 2024)
In the half of twentieth century, among newly emerging states on the map of the world, Pakistan was one of them. The creation of Pakistan was not an over-night phenomenon. It took years and many precious lives to make it practical. Right after the independence problems were waiting for the nascent state. At that time, there was dire need of charismatic leader however; the tiring freedom movement and health issues Jinnah’s charisma was getting faded away. It was the time to reshape the country by picking up the pieces from the beneath to put the state on the track of political development. Furthermore, many hopes were attached to political leadership. Due to political maneuvering in the country the leadership could not full-fill the wishes of common people. The study analyzed the early phases of political development in the newly born state. It also discussed the role of institutions regarding the development of the state how the country came under the troubled waters and how the top brass leadership of the country misused their powers to disrupt the political landscape of Pakistan. Key Words: Pakistan, Quaid-e-Azam, Leadership, Political development, 1951-1955.